PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMA NEGERI 1 SINGKEP PESISIR - Muhamad Argafar; Pauzi; Nurlaila Susanti (Sekolah Tinggi Ilmu Tarbiyah (STIT) Lingga, 2025)
This study aims to analyze the effect of using instructional media on students' learning motivation in the subject of Islamic Religious Education (PAI) at SMA Negeri 1 Singkep Pesisir. The background of this research is the low motivation of students in learning PAI, which is influenced by internal and external factors, particularly the school environment. The use of instructional media is expected to be a solution to increase students' interest and motivation to learn. This study employs a quantitative approach with a survey method. Data were collected through questionnaires distributed to 55 students as research samples. The Chi-Square test results showed a significant effect between the use of instructional media and learning motivation with an Asymp. Sig value of 0.001 < 0.05. The correlation test indicates that variable X (instructional media) and variable Y (learning motivation) have a perfect correlation, with a significance value of 0.01 < 0.05 and a Pearson correlation coefficient of 0.957, which falls within the perfect correlation range (0.81-1.00). The results of this study show that the use of instructional media has a significant effect on increasing students' learning motivation. These findings indicate that innovative and interactive instructional media can encourage students to be more active in the learning process, particularly in the subject of PAI. The study’s recommendations emphasize the importance of schools providing adequate instructional media facilities to support a more effective learning process.